Demographic data, comorbidities, quality of life, and survival probability of biologic therapy associated with sex-specific differences in psoriasis in the Czech Republic - Kojanova, Martina; Fialova, Jorga; Cetkovska, Petra; Dolezal, Thomas; Lomicova, Iva; Arenberger, Petr; Gkalpakiotis, Spyridon; BIOREP Study Group (Dermatologic therapy, 2021)
BIOREP is a Czech registry of patients with psoriasis undergoing biological treatment. The objective of the study was to compare differences in demographic data, previous therapy, comorbidities, severity of psoriasis, quality of life, drug survival rates, and reasons for discontinuation between men and women. We analyzed a cohort of patients from the registry treated between May 2005 and January 2020. The total study population of 2472 patients (4051 treatment series) included 913 females and 1559 males. Women were significantly older than men at the onset of the biological treatment (47.8 vs 45.4 years, P < .0012) and the mean durations of psoriasis and that from its diagnosis until initiation of biological therapy, were longer in women (29.6 vs 27.2 years and 23.2 vs 20.6 years, P < .0012). Women as compared with men were also more often diagnosed with psoriatic arthritis (43.5% vs 33.0%, P < .0012). The prevalence rate of comorbidities was equivalent for both sexes except for that of depression (11.4% females vs 3.7% males, P < .0012). Both the DLQI and PASI scores were significantly different at baseline (DLQI = 16.0 and PASI = 19.5 for men vs DLQI 17.6 = and PASI = 17.7 for women, P < .0012). The survival probability with biological therapy was significantly lower in women for both biologically naïve and non-naïve patients, and there was more evidence of adverse effects in women. Our research demonstrates significant differences relative to multiple factors associated with psoriasis between men and women.
Keywords: kvalita života; Male; registry; lidé; Psoriasis; Humans; stupeň závažnosti nemoci; pravděpodobnost; Biological Therapy; Probability; Quality of Life; psoriáza; biologická terapie; Czech Republic; mužské pohlaví; gender; Česká republika; ženské pohlaví; psoriasis; Severity of Illness Index; Female; biological treatment